Pengaruh Penggunaan Variasi Konsentrasi Perekat Kanji Terhadap Lama Bakar RDF-5 Ampas Kopi Dan Serbuk Kayu Sengon - Darmawan, Fuad Yanuar Widya; Wijayanto, Danar Susilo; Rohman, Ngatou (Nozel : Jurnal Pendididikan Teknik Mesin, 2021)
This research aims to determine the effect of the variations use of starch adhesive on the RDF-5 burn time from coffee ground and sengon sawdust. The method used in this research is experimental. Independent variables in this research are ratio of variations in composition of the ingredients are 0:100, 30:70, 50:50, 70:30, 100:0 and variations in concentration of adhesive are 10%, 20%, 30%. Dependent variables in this research is burn time. Control variables in this research are mesh, pressing pressure, and the resulting RDF-5 dimensions. This research was conducted in the Mechanical Engineering Education Laboratory of the UNS in Campus V. Data collection of burning time using stopwatch and blower. The longest burn time was found in 100:0 composition variation and 30% adhesive concentration. The result of research showed that the longest burn time produced by RDF- 5 which uses the most starch adhesive.